LEARNING PROCESS DURING THE COVID-19 PANDEMIC IN EARLY CHILDHOOD EDUCATION INSTITUTIONS IN THE CITY OF SAMARINDA - Hanita (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2022)
This study focuses on identifying how Early Childhood Education Institutions in the city of Samarinda carry out the learning process during the covid-19 pandemic. After the government rules to carry out learning from home. The emergence of learning from home rules makes educators have to keep innovating and being creative in carrying out the learning process. In order for children's rights to be fulfilled, the learning process from home is carried out online and offline. This study analyzes the learning process during the Covid-19 pandemic at the Early Childhood Education Institution. The method used is qualitative research with a descriptive approach, data collection techniques and research instruments using interview text using google form. This research uses triangulation technique. The results of the interviews were collected from seven Early Childhood Education Institutions, namely KB Al-Mardiah, KB Al-Hijrah, RA Mentari, TK Fastabiqul Khairat, TK Engang Putih, TK Tunas Harapan and TK Negri 11. The results of the identification of this study are 1) Child Education Institutions Early childhood in Samarinda City do a lot of digital learning processes or better known as online learning. What is considered closer to the face-to-face process, 2) assignments are still given in the form of student worksheets which are distributed at the beginning of the week and collected at the end of the week, and 3) meeting hours are much less with one hour meeting consisting of 10 minutes of opening, 40 minutes of core activities and 10 minutes closing. However, for offline learning, educators experience obstacles and difficulties, especially in understanding the implementation of the offline learning process and lack of good cooperation with parents.